The impact of season on heart rate variability and workload of workers in young tree tending operations of a Larix kaempferi (Lamb.) Carr. stand: a preliminary study. Issue 2 (4th May 2022) - Lee, Eunjai; Baek, Kigwang; Lee, Sangtae; Cho, Min-Jae; Choi, Yun-Sung; Cho, Koo-Hyun
ABSTRACT: Larix kaempferi (Lamb.) Carr. plantations are a reasonable alternative to timber production for producing high-quality wood for South Korean industrial applications that need appropriate and high-quality practice of silvicultural operations. Weeding and tree pruning operations, which can favor trees in their competition with vegetation, require intensive manual labor. Therefore, the objective of this study was to determine the effect of these operations on the heart rate variability, relative heart rate (RHR), and physical workload of workers in April (spring) and July (summer) months. Our results showed that the mean heart rate variability and RHR for weeding (108.0 bpm and 49.4%, and 105.8 bpm and 46.8% for worker A and B, respectively) and tree pruning (104.5 bpm and 46.1%, and 114.4 bpm and 55.9% for worker A and B, respectively) in July were higher than those in April. In addition, the level of workload in July was characterized as heavy to very heavy, and as moderate to heavy in April. The results from this study provide useful information for appropriate young tree tending operations from the perspective of the safety and health of workers.